The Effect of Store Atmosphere on Customer Satisfaction at the Semangat Baru Namrole Billiards Business - Dourstygo Novenry Lesnussa; Mochammad Kresna Noer (Riviera Publishing, 2026)
The entertainment and leisure sector business is currently experiencing rapid growth, including billiards venues that have evolved from mere gaming facilities to social spaces for customers to gather, relax, and build relationships. In this competitive landscape, business owners must not only provide quality gaming facilities but also create a comfortable, attractive, safe, and customer-oriented environment that matches the preferences of local customers. Namrole's New Spirit Billiards operates with a distinctive open ventilation concept that allows natural air flow into the business premises, creating a cool environment without relying on air conditioning or fans, equipped with a strategic location in front of the district/city road, the availability of snacks, coffee, noodles, and bread, as well as a free game bonus 15 minutes after booking one hour. This study aims to analyze the influence of store atmosphere on customer satisfaction in Namrole's New Spirit Billiards business. This research used a quantitative approach with a survey method by distributing questionnaires to customers. The independent variable is store atmosphere, while the dependent variable is customer satisfaction. Data analysis techniques include validity test, reliability test, classical assumption test, simple linear regression analysis, t-test, and coefficient of determination. The results are expected to show that store atmosphere has a positive effect on customer satisfaction. This study provides practical implications for the management of Billiard Semangat Baru Namrole to maintain a natural, simple, strategic, and customer-friendly atmosphere as a strategy to increase customer satisfaction and loyalty.